COVID-19 in patients with chronic kidney disease stage 5 - Dudar, I.; Krasyuk, E.; Shymova, A.; Hryhorieva, Y.; Malasaiev, M.; Fierients, O.; ShifrisІ.; Savchuk, V.; BurzhynskaІ.; Prusskyi, F. (Ukrainian Journal of Nephrology and Dialysis, 2021)
The study aimed to determine the frequency of COVID-19, specific of process and the mortality rate among dialysis patients with COVID-19. Materials and methods: The retrospective study included 764 patients with CKD VD, who received dialysis treatment at the Kyiv City Center for Nephrology and Dialysis, which is the clinical base of the Institute of Nephrology of the National Academy of Medical Sciences since September 1, 2020. until December 31, 2020. 155 patients were diagnosed with coronavirus disease. The study was conducted in two stages. In the first stage, dialysis patients with coronavirus disease were divided into groups depending on the severity of the disease. The second stage of the study was determined the influence of age, duration of dialysis treatment, gender, cause of chronic kidney disease VD, obesity, diabetes mellitus and cardiovascular pathology on the course of coronavirus disease, as well as complications and mortality from COVID-19 among the dialysis population. Results: 155 cases of COVID-19 were registered among 764 dialysis patients. Mild coronavirus disease was diagnosed in 38 (24.5%) patients, moderate and severe in 64 (41.3%) and 53 (34.2%) patients, respectively. Oxygen support was required for 76 patients (79%), and artificial lung ventilation was used for 17 (10.9%) patients. Factors associated with severe coronavirus disease in this category of patients were found to be obesity (BMI> 30 kg / m2), diabetes mellitus, concomitant cardiovascular disease, and the need for oxygen support. In this category of patients, obesity (BMI>30 kg/m2), cardiovascular disease, diabetes mellitus and require supplement oxygen are associated with severe Coronavirus disease COVID-19. There was no significant effect on the severity of coronavirus disease in the age of patients and duration of dialysis treatment. The duration of treatment in patients with diabetes was significantly higher (p <0.05), a direct strong correlation between BMI and duration of treatment was demonstrated. Survival was significantly higher in the group of patients who did not require oxygen support (78% vs. 56%) and had a BMI <30 kg / m2 (87% vs. 37%). Conclusions: the incidence of coronavirus disease among the dialysis cohort was 20.2% of cases. Patients treated with peritoneal dialysis had a significantly lower incidence. Severe coronavirus disease has been associated with obesity, cardiovascular disease, and the need for oxygen support. Men were more likely to have COVID-19 than women. There is no connection between the severe course of coronavirus disease with the age of patients and the duration of dialysis treatment. The duration of treatment of Coronavirus disease in the group of patients with diabetes and high BMI was longer. The following complications predominated in patients with COVID-19: thrombosis of arteriovenous fistula and atrial fibrillation. During the study period, 20 (12.9%) deaths were registered. Patient survival was higher in the group of patients without oxygen support and with a lower BMI.